Ferromagnetic–antiferromagnetic coupling core–shell nanoparticles with spin conservation for water oxidation - Ge, Jingjie (2022)
Rational design of active oxygen evolution reaction (OER) catalysts is critical for the overall efficiency of water electrolysis. The differing spin states of the OER reactants and products is one of the factors that slows OER kinetics. Thus, spin conservation plays a crucial role in enhancing OER performance. In this work, ferromagnetic (FM)-antiferromagnetic (AFM) Fe3 O4 @Ni(OH)2 core-shell catalysts are designed. The interfacial FM-AFM coupling of these catalysts facilitates selective removal of electrons with spin direction opposing the magnetic moment of FM core, improving OER kinetics. The shell thickness is found critical in retaining the coupling effect for OER enhancement. The magnetic domain structure of the FM core also plays a critical role. With a multiple domain core, the applied magnetic field aligns the magnetic domains, optimizing the electron transport process. A significant enhancement of OER activity is observed for the multiple domain core catalysts. With a single-domain FM core with ordered magnetic dipoles, the spin-selective electron transport with minimal scattering is facilitated even without an applied magnetic field. A magnetism/OER activity model therefore hypothesizes that depends on two main parameters: interfacial spin coupling and domain structure. These findings provide new design principles for active OER catalysts.